Metacognitive Abilities as a Protective Factor for the Occurrence of Psychotic-Like Experiences in a Non-clinical Population - Giugliano, Marco; Contrada, Claudio; Foglia, Ludovica; Francese, Francesca; Romano, Roberta; Dello Iacono, Marilena; Di Fausto, Eleonora; Esposito, Mariateresa; Azzara, Carla; Bilotta, Elena; Carcione, Antonino; Nicolò, Giuseppe (Frontiers in Psychology, 2022)
Psychotic-like experiences (PLEs) is a phenomenon which occurs in general population experiencing delusional thoughts and hallucinations without being in a clinical condition. PLEs involve erroneous attributions of inner cognitive events to the external environment and the presence of intrusive thoughts influenced by dysfunctional beliefs; for these reasons, the role played by metacognition was largely studied. This study investigates PLEs in non-clinical population and discriminating factors involved in this kind of experiences, among which metacognition as well as psychopathological features seems to have a crucial role. The aim of the present work was to extend the knowledge about the relationship between metacognition, psychopathology, and PLEs, orienting the focus on metacognitive functioning. The sample consisted of 207 Italian participants (M=32%, F=68%) voluntarily recruited online, who gave consent to participate in the study. The average age of the sample was 32.69 (SD 9.63; range 18-71). Subjects affected by psychosis, neurological disease, and drug addiction were excluded from the analyses. The following scales were used to investigate PLEs: PDI, LSHS-E, PQ-B, RHS. In order to assess general psychopathological features, the scale BASIS-32 was administrated. The Metacognition Self-Assessment Scale (MSAS) was chosen to evaluate metacognitive functioning. From hierarchical regression analyses it emerged that the presence of anxiety, depressive and impulsive/addictive symptoms constitute a remarkable vulnerability factor for PLEs, in line with previous evidence regarding the relationship between general psychopathology and PLEs. Metacognition negatively predicts PLEs and its presence does not affect the significance of psychopathological variables, this suggests that metacognitive abilities seem to play a protective role for the occurrence of PLEs among non-clinical individuals, and such ability operates as an independent predictor along with other variables.